Real estate investment companies in Turkey as a financial tool - Güven, Tuna (My University, 2002)
Gecekondulaşmanın devam etmesi, ülkemizde halen konut açığı bulunduğunu göstermektedir.Nufus artışından ve göçten kaynaklanan knut gereksinimi ile konut üretimi arasında açık bir dengesizlik bulunmaktadır Gecekonduyu bir sorun olarak değil, yetersiz üretim karşısında, halk tarafından üretilmiş çözüm olarak ele almak gereklidir. Tezin amacı GYO’lar yoluyla sermaye piyasalarından konut sektörüne nasıl kaynak aktarılacağına dair fikir üretmektir. Eğer yatırımcıya yönelik olarak, GYO’ lara yaptıkları yatırımda vergi muafiyeti sağlanırsa, GYO’ lara yatırım desteklenmiş olur. GYO’ların kurumlar vergisi muafiyeti de topladıkları fonları konut ağırlıklı projelere aktarmaları şartına bağlanırsa, konut projelerine uygun ve ucuz fon sağlanabilir. İlk bakışta, vergi gelirlerinde bir düşüş olacağı düşünülse de, subvanse edilmeyen konut projelerinden ve gecekondulaşmaya ayrılan fonlardan edilecek tasarrufların toplamı bahsi geçen vergi gelirleirndeki kayıbı kapatmaya yetecek düzeyde bir harcama düşüşü sağlanabilir.

The existence of squatter problem in Turkey is the indicator of current and ongoing housing deficit. There is distinct imbalance between housing demand and supply due to pace of growth and immigration and insufficient supply. Simply, in the case of insufficient supply public draw with squatters. Against taking into account squatters as problem, it should be accepted it as solution which public drew . The core of subject seems inefficiency of financing techniques for housing production. The objective of the thesis is to put forward an idea about an alternative solution, which will enable transferring funds from capital markets to housing sector via Real Estate Investment Companies. If conditional tax shelters can be stated for investor, investors would be led to invest in REICs that will cause to accumulate more funds than common. If REIC transfer the accumulated funds to housing projects, it can benefit from corporate tax deduction. If not, REIC will become an ordinary corporation about taxation. As a consequence, investors will invest on REICs just in order to benefit from tax deduction regardless where their funds transferred to and REICs will make inexpensive or available the excess funds for housing projects. Though it seems to cause a loss in collected tax, it would be resulted an explosion in housing production that is strongly useful in to lessen deficit. In first, it seems to cause a loss in collected tax, sum of saving from unsubsidised housing production and less expense for squatter could be greater than uncollected tax.
Keywords: Ev ekonomisi ve aile yaşamı; Konut; Konut Politikası; Konutlar ve konut donanımı